Super-Resolution Quantification of T2DM-Induced Mitochondrial Morphology Changes and Their Implications in Pharmacodynamics of Metformin and Sorafenib - Du, Yang; Zhu, Ya-Juan; Zeng, Bo; Mu, Xiao-Li; Liu, Ji-Yan (Frontiers in Pharmacology, 2022)
Mitochondria, as the powerhouse of cell, is involved in various processes of cellular homeostasis, especially energy metabolism. The morphology of mitochondria is a critical indicator for its functions, referring to mitochondrial fusion and fission. Here, we utilized a structured illumination microscopy (SIM) to measure the mitochondrial morphology in living cells. Benefitting from its nanoscale resolution, this SIM-based strategy can quantify the fusion and fission of mitochondria with high sensitivity. Furthermore, as type 2 diabetes mellitus (T2DM) is caused by disorder of energy substrate utilization, this strategy is potential to study T2DM through analyzing the mitochondrial morphology of insulin-resistant (IR) cells. With SIM, we found that the mitochondrial fission was increased in IR MRC-5, LO2, FHs 74 Int and HepG2 cells, but not in IR Huh7 cells with high-invasiveness ability. Furthermore, we found that metformin could inhibit mitochondrial fission in IR cells, and sorafenib could promote mitochondrial fusion in HepG2 cancer cells, especially in those IR cells. To conclude, mitochondrial fission is involved in T2DM, and the cancer cells with high-invasiveness ability may be equipped stronger resistance to energy metabolism disorder. In addition, the pharmacodynamics of metformin and sorafenib in cancer may be related to inhibition of mitochondrial fission, especially for patients with T2DM.